Factors associated with wasting among pediatric cancer patients aged 2–17 years at Uganda cancer institute: A cross-sectional study - Daisy Wannyana; Arthur Bagonza; Sandrah Joyce Mwima; Christine Nalwadda; Rawlance Ndejjo (PLoS ONE, 2025)
Introduction Wasting is a major concern among pediatric cancer patients and significantly affects treatment outcomes and quality of life. However, limited data exist on the prevalence of wasting and its associated factors in low-income contexts. This study determined the prevalence of wasting and its associated factors among pediatric cancer patients aged 2--17 years at the Uganda Cancer Institute. Methods An institutionally based, cross-sectional study was conducted among 270 systematically randomly selected caregiver‒child pairs. Univariate, bivariate, and multivariable analyses were conducted using STATA version 14. Variables with p-value < 0.05 were considered statistically significant. Results Among 270 pediatric cancer patients aged 2–17 years, 27.4% (n = 74) were wasted. Children aged 5 years and older had a 20% higher prevalence of wasting (aPR = 1.2; p = 0.002). Cancers near the gastrointestinal tract were associated with a 10% greater prevalence of wasting (aPR = 1.1; p = 0.028). Wasting was lower by 20% among children whose caregivers had tertiary education (aPR = 0.8; p = 0.002), whereas treatment effects increased wasting prevalence by 10% (aPR = 1.1; p = 0.013). Conclusion Wasting is a prevalent form of malnutrition among pediatric cancer patients requiring the integration of nutritional services to address the nutritional needs of children, especially those aged greater than 5 years, those with cancers along the gastro-intestinal tract and those experiencing treatment effects. Additionally, health and nutrition education programs tailored to the caregiver’s level of education are needed.